Kinematic stability in cardiac locomotor synchronization during regular walking - Kibushi, Benio (Frontiers in Physiology, 2024)
In locomotion, previous studies have identified a phenomenon known as cardiac locomotor synchronization (CLS), characterized by the phenomenon where heartbeats consistently occur at a specific time within the locomotor cycle. While the physiological significance of CLS is well recognized, its kinematic benefits remain uncertain. Therefore, this study aimed to elucidate the kinematic benefits of CLS under regular walking. Smoothness of walking and local dynamic stability was assessed through the RMS of center of mass acceleration (RMS-CoMacc) and maximum Lyapunov exponent (maxL). It was hypothesized that stronger CLS would lead to reduced RMS-CoMacc and maxL. Thirteen participants performed a 10-minute walk at 5.0 km/h. The electrocardiogram and the motion capture data were recorded. To evaluate the CLS, phase coherence (λ) between cardiac and walking step rhythm was computed. The high and low-phase coherence was defined as λ ≥ 0.1 (λhigh) and λ < 0.01 (λlow); corresponding RMS-CoMacc and maxL values were compared for each state. Although the λhigh was significantly higher than λlow, no significant differences in RMS-CoMacc and maxL were observed between the high and low states. The relatively weak CLS observed herein might not have led to a reduction in RMS-CoMacc and maxL. In addition, regular walking speed might be a velocity at which it is challenging to generate intervention effects. Hence, the CLS appears to have negligible impact on the smoothness of walking or local dynamical stability at a 5.0 km/h.